Child-Centered Collaborative Conversations That Maximize Listening and Spoken Language Development for Children with Hearing Loss - Garber, Ashley S.; Nevins, Mary Ellen (Seminars in Speech and Language, 2012)
In the period that begins with early intervention enrollment and ends with the termination of formal education, speech-language pathologists (SLPs) will have numerous opportunities to form professional relationships that can enhance any child's listening and spoken language accomplishments. SLPs who initiate and/or nurture these relationships are urged to place the needs of the child as the core value that drives decision making. Addressing this priority will allow for the collaborative conversations necessary to develop an effective intervention plan at any level. For the SLP, the purpose of these collaborative conversations will be twofold: identifying the functional communication needs of the child with hearing loss across settings and sharing practical strategies to encourage listening and spoken language skill development. Auditory first, wait time, sabotage, and thinking turns are offered as four techniques easily implemented by all service providers to support the child with hearing loss in all educational settings.
Keywords: Collaborative conversations; communicative feedback; purposeful communicative interactions; auditory strategies